Delivery strategies of messenger RNA therapeutics for brain disorders - Youn, Kounghwa; Oh, Sunmin; Gil, Hyunchae; Choi, Yongseok; Keum, Gyochang; Bang, Eun-kyoung (대한화학회, 2025)
Messenger RNA (mRNA) therapeutics have substantial potential in modern medicine, such as brain disorder treatment, following the success of mRNA vaccines against coronavirus disease 2019 (COVID-19). Their ability to drive endogenous protein production makes them highly versatile, but clinical translation for brain disorders faces major obstacles. The blood–brain barrier (BBB), rapid enzymatic degradation, and inefficient cellular uptake still remain key challenges preventing efficient delivery of mRNA therapeutics. To overcome these hurdles, diverse carrier systems were used. Lipid nanoparticles, polymeric carriers, and exosome-based carriers provide mRNA protection from enzymatic degradation and facilitate efficient uptake into target cells. Furthermore, conjugation with brain-targeting ligands is under development to enhance BBB penetration and brain selectivity. This review summarizes the delivery of RNA therapeutics for the treatment of brain disorders published over the past 5 years, categorized by administration route. Direct injection bypasses the BBB and ensures local delivery but is invasive and clinically limited. Systemic administration offers a less invasive option, leveraging passive, and active delivery mechanism. Immune cell-mediated brain cancer treatment is also promising, enabling engineered immune cells to cross or circumvent the BBB. In parallel, peripheral delivery routes, including intranasal and intratympanic injections, are being explored to exploit alternative pathways to the brain. Although no mRNA therapeutics for brain disorders have been approved, preclinical and early clinical studies demonstrate considerable potential. Continued innovation in carrier design, administration routes, and molecular engineering is expected to reveal safe and effective mRNA therapeutics for previously untreatable brain disorders. We hope that this review will offer valuable insights into the development of next-generation mRNA delivery platforms for brain disorders by summarizing current brain-targeted mRNA delivery strategies.